Cardiomyocyte Proliferation and Maturation: Two Sides of the Same Coin for Heart Regeneration - Zhao, Ming-Tao; Ye, Shiqiao; Su, Juan; Garg, Vidu (Frontiers in Cell and Developmental Biology, 2020)
In the past few decades, cardiac regeneration has been the central target for restoring the injured heart. In mammals, cardiomyocytes are terminally differentiated and rarely divide during adulthood. Embryonic and fetal cardiomyocytes undergo robust proliferation to form mature heart chambers in order to accommodate the increased workload of a systemic circulation. In contrast, postnatal cardiomyocytes stop dividing and initiate hypertrophic growth by increasing the size of the cardiomyocyte when exposed to increased workload. Extracellular and intracellular signaling pathways control embryonic cardiomyocyte proliferation and postnatal cardiac hypertrophy. Harnessing these pathways could be the future focus for stimulating endogenous cardiac regeneration in response to various pathological stressors. Meanwhile, patient-specific cardiomyocytes derived from autologous induced pluripotent stem cells (iPSCs) could become the major exogenous sources for replenishing the damaged myocardium. Human iPSC-derived cardiomyocytes (iPSC-CMs) are relatively immature and have the potential to increase the population of cells that advance to physiological hypertrophy in the presence of extracellular stimuli. In this review, we discuss how cardiac proliferation and maturation are regulated during embryonic development and postnatal growth, and explore how patient iPSC-CMs could serve as the future seed cells for cardiac cell replacement therapy.